2015
DOI: 10.5194/bg-12-5831-2015
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility controls soil–atmosphere carbon dioxide and methane fluxes in a tropical landscape converted from lowland forest to rubber and oil palm plantations

Abstract: Abstract. Expansion of palm oil and rubber production, for which global demand is increasing, causes rapid deforestation in Sumatra, Indonesia, and is expected to continue in the next decades. Our study aimed to (1) quantify changes in soil CO 2 and CH 4 fluxes with land-use change and (2) determine their controlling factors. In Jambi Province, Sumatra, we selected two landscapes on heavily weathered soils that differ mainly in texture: loam and clay Acrisol soils. In each landscape, we investigated the refere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
128
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(149 citation statements)
references
References 46 publications
16
128
5
Order By: Relevance
“…Thus, changes in soil N-oxide fluxes can be attributed to land-use change with its associated management practices. The plantations' ages ranged between 7 and 17 years, and tree density, tree height, basal area and tree species abundance were higher in the reference land uses than the monoculture plantations (all reported by Allen et al, 2015;Hassler et al, 2015;Kotowska et al, 2015).…”
Section: Study Area Experimental Design and Management Practicesmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, changes in soil N-oxide fluxes can be attributed to land-use change with its associated management practices. The plantations' ages ranged between 7 and 17 years, and tree density, tree height, basal area and tree species abundance were higher in the reference land uses than the monoculture plantations (all reported by Allen et al, 2015;Hassler et al, 2015;Kotowska et al, 2015).…”
Section: Study Area Experimental Design and Management Practicesmentioning
confidence: 97%
“…2.2) were conducted in 2013 (Appendix Table A1). A more detailed description of the study sites and plot design was reported earlier by Allen et al (2015) and Hassler et al (2015).…”
Section: Study Area Experimental Design and Management Practicesmentioning
confidence: 99%
See 3 more Smart Citations